The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5267/j.msl.2021.1.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing police integrity by exploring causes of police corruption

Abstract: Methods for the elimination of police corruption to enhance integrity, usually disregards its roots that are connected to societal elements in light of the fact that police corruption has societal causes and implementing a change of the police needs, to certain degree, transforming the community. In this research, a qualitative approach (semi-structured interviews, focus group meetings and observations) was used the analysis methods from social profiles categorized as per their degree of police corruption util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
2
7
1
Order By: Relevance
“…Extortions and bribes are reported among police officers who use the power of the police and adopt the extra-legal acts (Singh, 2022). Khan et al (2021) also supports the findings of Singh ( 2022), and Malik and Qureshi (2021) also make the case that the PSP uses its official de-jure influence for de-facto gains.…”
Section: 3supporting
confidence: 80%
“…Extortions and bribes are reported among police officers who use the power of the police and adopt the extra-legal acts (Singh, 2022). Khan et al (2021) also supports the findings of Singh ( 2022), and Malik and Qureshi (2021) also make the case that the PSP uses its official de-jure influence for de-facto gains.…”
Section: 3supporting
confidence: 80%
“…He argued that this situation makes people and organizations develop learning as a whole, providing transparency, consistency, coherence, and commitment. However, in a separate study by Khan et al (2021), the outcomes revealed that none of these aspects of integrity can be fully realized in the individual or in an organization. Integrity is also known as a term for a continual learning process with the person discovering more about the different aspects of the self and others and how these two connect (Robinson & Dowson, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…The Intelligent Transportation System (ITS) is a sophisticated network of technologies and infrastructure designed to improve transportation systems' safety, efficiency, and sustainability. The Intelligent Transportation System (ITS) is a theoretical framework that integrates transportation infrastructure with information and communication technology to enhance its effectiveness, safety, and sustainability (Laksana, 2019;Suthanaya, 2023) Regarding security, ITS can employ communication technology to enable interaction between infrastructure and vehicles (Huang et al, 2017;Khan et al, 2021). A collision notification system can be installed in a vehicle, automatically transmitting signals to the control center in the event of an accident.…”
Section: Intelligent Transportation Systemmentioning
confidence: 99%